Correlation Between Insight and Capacity to Consent to Research in Subjects With Bipolar Disorder Type I and Schizophrenia (2016)
Introduction Schizophrenia and bipolar disorder type I (BD-I) can affect patient autonomy and capacity to consent to participate in research. Other variables associated with the autonomy of patients must be explored in order to improve the quality of the currently available tools. Objective To evaluate the relationship between insight and the capacity to consent to participate in research in patients with BD-I and schizophrenia. Methods A cross-sectional and longitudinal study was conducted with 120 subjects (40 subjects with schizophrenia, 40 with BD-I, and 40 healthy controls). The tools used were the Scale Assessment Insight-Expanded (SAI-E) and the MacArthur Competence Assessment Tool-Treatment (MacCAT-CR), which was first adapted culturally, and its validity and reliability assessed. The results obtained on each scale were compared and the association between them were evaluated. Results There is a direct correlation between the capacity to consent to research, measured using the MacCAT-CR tool, and the degree of insight, measured using the SAI-E scale, with an effect size of 1.3 for BD-I and 2.03 for schizophrenia. Conclusions The results suggest that there is a correlation between the degree of insight and the capacity to consent to research in subjects with schizophrenia and BD-I. Insight should therefore be included as a relevant variable to assess the capacity to consent, and future studies should include it when researching on or designing new tools which aim at a greater respect of patient autonomy. © 2016 Asociación Colombiana de Psiquiatría